Determinant Factors Related to Nurse Satisfaction at Tabanan Regency Hospital - Prataba, I Made Dwi Krisma; Kamaryati, Ni Putu; Rahayuni, I Gusti Ayu Rai; Astawa, I Gede Satria (International Journal of Science and Society, 2025)
Job satisfaction is a crucial aspect in the performance of health workers, especially nurses, because it affects the quality of service and work outcomes. Nurses who feel job satisfaction tend to provide optimal service according to their competence. This study aims to identify factors associated to nurses' job satisfaction and determine the most influential variables in Tabanan Regency Hospital. This study used a descriptive correlational design with a cross-sectional approach. The sample consisted of 172 nurses selected through purposive sampling techniques. Data were collected using a standardized questionnaire that had been tested for validity and reliability. Analysis was conducted univariately, bivariately using the Chi-square test, and multivariately with binary logistic regression. Bivariate analysis showed a significant relationship between work motivation (p=0.009) and reward system (p=0.033) with job satisfaction. Multivariate analysis identified work motivation as the dominant factor with odds ratio (OR) of 4.424 (95% CI: 1.309–14.952). Work motivation was shown to be a major determinant of nurse’ job satisfaction. Managerial interventions that focus on improving internal and external motivation are expected to increase nurses' job satisfaction, which in turn has a positive impact on the quality of nursing services.